Pedagogy of Children during Preschool Education Intellectual Development through Support Psychological and Didactic Aspects (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Today, the development of the intellectual potential of preschoolers is one of the urgent issues. This article highlights the current issues of developing and improving the intellectual potential of preschoolers.